The Formation of Internal Reporting by Responsibility Centers - Kvasha, O. O.; Korobkina, I. S.; Shekhovtsova, D. D. (Statistics of Ukraine, 2018)
The article focuses on the aspects of the formation managerial internal reporting by the centers of responsibility. It was found out that the qualitative accounting and analytical support of enterprise management contributes to the development of a special informational system. Such a system should meet the requirements of management on the basis of the corresponding database and make the processing of data cheaper. It is substantiated that the achievement of the symbiotic relationship of management functions with the accounting process is possible on the basis of the application of a comprehensive goal approach, which is preceded by the separation of responsibility centers, the formation of the set of indicators and certain forms of internal reporting. The use of this approach during the organizing of managerial accounting at the enterprise makes it possible to cover by accounting system whole set of objects of management influence. The set of indicators that are to be transferred from the primary accounting and the procedures necessary for their further processing and the formulation of the internal managerial reporting according to the choice of the model of the managerial accounting have been received. The managerial report on the implementation of the budget by the responsibility centers for catering business enterprises is proposed. The technique of conducting the primary accounting which ensures the formation of the composition indicators of cash flows from the center of responsibility is provided. It is determined that a number of delivery received from other enterprises may not yet be paid during the operational internal reporting of the cash flow. The identification of the payments when they are paying in the next period is carried out on dates and numbers of business transactions. With this purpose the information transmission scheme for the identification of the payments for purchased products by catering business enterprises is proposed. It is also determined that the management’s current report is the Cash Flow Statement on Responsibility Centers. According to the report the executive management can evaluate the results of the work of the subdivisions and determine the direction of activities that generate the main cash receipts. The main improvement of the system of internal reporting is the provision of management needs, therefore the constraints and weaknesses of the reporting forms may change. Management reporting should allow the possibility of further analysis with a minimum of time, which is a sign of analyticity, draw conclusions and make economically sound management decisions on their basis.